On the Ritt condition on Locally Convex Vector Spaces - Akrym, A.; El Bakkali, A.; Faouzi, A. (Methods of Functional Analysis and Topology, 2021)
In this paper, we show that the Ritt condition in the case of locally convex spaces can be related to the power boundedness of a universally bounded operator. We will characterize this condition by two geometric properties of the powers and we prove that the Ritt condition will be shown to be equivalent to the Tadmor condition. We study the Ritt condition for a quasinilpotent operator acting on locally convex spaces. Also, an upper bound for the norm of the powers of operators acting on locally convex spaces under Ritt condition was given. Показано, що у випадку локально опуклих просторів умова Рітта пов’язана з обмеженістю степенів універсально обмеженого оператора. Ця умова характеризується в термінах геометричних властивостей степенів. Доведено, що умова Рітта еквівалентна умові Тедмора. Досліджена умова Рітта для вирадку квазінільпотентних операторів у локально опуклих просторах. Знайдена також верхня оцінка норм степенів операторів, які задовольняють умову Рітта.